Rotational structures in doubly odd 198Tl - Mariscotti, M. A. J.; Kreiner, A. J.; Fenzl, M.; Lunardi, S. (Elsevier B.V., 1977)
Fil: Mariscotti, M. A. J. Comisión Nacional de Energía Atómica; Argentina